Burning Nettle (Urtica urens) Germination and Seedbank Characteristics in Coastal California. Issue 4 (December 2016) - Lati, Ran N.; Shem-Tov, Shachar; Fennimore, Steven A.
Abstract : Burning nettle is a noxious weed that commonly infests coastal California vegetable fields. Weed control programs for lettuce and fresh spinach grown in this area do not adequately control burning nettle, and escaped weeds that mature are highly problematic during hand weeding and harvesting. Information on the biology and ecology of burning nettle is limited, and work was conducted to develop information about this weed. The objectives of this study were to evaluate the effect of temperature on burning nettle germination and to determine its base temperature value, to characterize the germination pattern of this weed and seedbanks under local California coastal conditions, and to estimate the optimal timing for burning nettle removal by herbicides and physical methods. The upper optimal temperature for burning nettle germination was 22.8 C, but there was no difference in the final germination percentage between 4 and 22.8 C. The base temperature was determined to be 3 6 0.2 C, and this information allowed the development of temperature-based optimal control timing models. In the field, burning nettle emerged throughout the year without any seasonal pattern, and germinable seeds were also found in the seedbank throughout the year. Burning nettle was able to complete a growth cycle throughout the year in coastal California. Burning nettle has a short growth cycle that allows it to set viable seeds within 466 6 13 growing degree days (GDD), and this timing is critical for burning nettle removal by herbicides, cultivation, or hand weeding. The optimal timing for phenmedipham application at 180 g ai ha –1 was estimated to be 205 GDD. The germination and seedbank field studies indicate why burning nettle is so well adapted to the mild climate of coastal California. However, results presented here suggest strategies to reduce the burning nettle seedbank, improve its control, and allow more efficient lettuce and fresh spinach production.